Oral Health among Residents of Publicly Supported Housing in Boston - Maxwell, Nancy Irwin (Springer US, 2013)
Tooth loss in adults diminishes quality of daily life, affecting eating, speaking, appearance, and social interactions. Tooth loss is linked to severe periodontitis and caries; and to risk of stroke, cardiovascular disease, rheumatoid arthritis, and dementia. At the national (USA) level, poverty and African-American race have been linked to lower utilization of dental services, suggesting that the 7.5 million residents of publicly supported housing may be at risk of tooth loss and poor overall oral health. We assessed whether residence in publicly supported housing in Boston was associated with four oral health-related indicators. Compared to residents of nonpublicly supported housing, after adjusting for covariates residents of both public housing developments (PHDs) and rental assistance units (RAUs) had significantly lower odds of having had a dental cleaning in the past year (PHD, OR = 0.64 (95 % CI, 0.44–0.93); RAU, OR = 0.67 (95 % CI, 0.45–0.99))—despite parity in having had a past year dental visit. Further, residents of RAUs had double the odds of having had six or more teeth removed (OR = 2.20 (95 % CI, 1.39–3.50)). Associations of race/ethnicity and housing type with dental insurance were interrelated. Unadjusted results document a deficit in oral health-related indicators among public housing residents, taken as a group, giving a clear picture of an oral health care gap and identifying a defined real-world population that could benefit from services. Existing public housing infrastructure could provide both a venue and a foundation for interventions to reduce oral health disparities on a broad scale.